Therapeutic lymphangiography for refractory post-operative chylous ascites in children: Can a needle replace the knife? - Sachit Anand; Apoorv Singh; Anjan Kumar Dhua; Vishesh Jain; Minu Bajpai; Priyanka Naranje; Devasenathipathy Kandasamy; Rakesh Kumar (Elsevier, 2020)
Chylous ascites is a rare but well-known complication following surgeries involving extensive dissection of the retroperitoneal structures. It is noticed in children primarily after oncological resections. Meanwhile, conservative treatment is paramount in its management; refractory cases generally require an aggressive approach. A rare case of refractory chylous ascites in a two-year-old boy occurring after excision of recurrent retroperitoneal neuroblastoma is being reported. The child underwent therapeutic lymphangiography with ethiodized oil, as an alternative to surgery, to tackle the refractory post-operative chyle leak. A prompt response was noticed and no recurrence of ascites has been observed during a 15-month follow-up.